Air weapon injuries in children: a case for education. Issue 1 (March 1985) - Robson, W J; Kumar, K
Abstract : The results of the first 6 months of a 2-year prospective study on the frequency, severity and methods of prevention of air weapon injuries to children are reported. Twenty-eight cases presenting to an urban paediatric accident and emergency department have been analysed. Nineteen of these were males between the ages of 10 and 16 years. At least 18 incidents occurred in public places. The five most serious injuries were of the orbit, face and abdomen. Another nine injuries were near vital structures. Education is needed on the existing guidelines for the safe use of air weapons.